Hydrogenation and hydrogen intercalation of hexagonal boron nitride on Ni(1 1 1): reactivity and electronic structure. (3rd August 2017) - Späth, F; Gebhardt, J; Düll, F; Bauer, U; Bachmann, P; Gleichweit, C; Görling, A; Steinrück, H-P; Papp, C
Abstract: We investigate the reactivity of hexagonal boron nitride (h-BN) on a Ni(1 1 1) single crystal towards atomic hydrogen over a wide exposure range. Near edge x-ray absorption fine structure and x-ray photoelectron spectroscopy (XPS) show that for low hydrogen exposures hydrogenation of the h-BN sheet is found. In contrast, intercalation of hydrogen between h-BN and the Ni(1 1 1) substrate occurs for high exposures. For intermediate regimes, a mixture of intercalation and hydrogenation is observed. From temperature-programmed desorption and temperature-programmed XPS experiments, we conclude that the hydrogen covalently bound to h-BN is rather stable with a desorption temperature of 600 K, while intercalated hydrogen is desorbing already at 390 K. Further insight into the structural arrangements and the thermodynamics of the system is obtained by comparing our experimental results with extensive density-functional theory calculations. Together with ultraviolet photoelectron spectroscopy measurements, the calculations provide detailed insight into the influence of hydrogenation on the electronic structure of h-BN.